Public-private partnership and national innovation systems in the right of foreign countries - Kunitskaya, Olga (Journal of the Belarusian State University. Law, 2019)
The article analyzes the impact of legislative initiatives on improving national innovation systems of some foreign countries with innovative economies on the formation of public-private partnership in the field of innovation. In the Republic of Belarus, the issue of determining the legal nature of public-private partnership in the sphere of innovative activity, the main features of its legal regulation in connection with the formation of a national innovation system has not yet been resolved. This makes it possible to draw a conclusion about the scientific feasibility and practical necessity of studying the foreign experience of the legal regulation of public-private partnership in the sphere of innovation activities of those countries that have successfully implemented public-private partnership over a long period of time. This research is based on the position that, on the one hand, effective national innovation systems of foreign countries contribute to the development of public-private partnership in the field of innovation, and on the other hand, public-private partnership can become the basis for improving the national innovation system of the state. The research is carried out taking into account the results of the rethinking of the scientific doctrine of the legal regulation of public-private partnership and innovation that has been developed to date, which is necessary for the further updating of the relevant legislation, the elimination of existing legal gaps and collisions, the development of basic approaches to the legal regulation of public-private partnership in the field of innovation activities.